The Relation Between a Prior Earnings Forecast by Management and Analyst Response to a Current Management Forecast. - Williams, Patricia A. (The Accounting Review, 1996)
This paper investigates whether the accuracy of a prior earnings forecast by management serves as an indicator to analysts of the believability of a current management forecast. Regression analysis is used to examine the relationship between the usefulness of a prior forecast by management and analyst response to a current forecast, after controlling for other determinants of believability. The results suggest that management establishes a forecasting "reputation" based on prior earnings forecasts.